Kiais without Pesantren and the Construction of Local Wisdom for Peace in Multicultural Settings - Kholish, Moh Anas; Harwanto, Aditya Putra; Ningtias, Ratih Kusuma; Ali, Mahrus (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2026)
Existing studies on Islamic leadership in Indonesia heavily focus on pesantren-based kiais, highlighting institutional authority as the primary source of religious legitimacy. This study addresses the limited attention received by non-institutional religious actors by examining the role of kiais without pesantren in constructing local wisdom values for peacebuilding in multicultural settings. Using a phenomenological approach, this research was conducted in three different locations: Wagir (Malang Regency), Polehan (Malang City), and Bali. Data were extracted from in-depth interviews and participant observation involving three key informants actively engaged in interreligious interaction. The findings reveal three main patterns. First, religious authority is constructed through social proximity and moral credibility rather than formal institutional affiliation. Second, these kiais employ dialogical and mediative strategies, particularly listening-based engagement and informal conflict resolution, in managing interreligious conflict. Third, they develop contextual interpretations of Islamic teachings by adapting religious practices to local cultural norms to sustain social harmony. This study theoretically extends the concept of religious authority beyond institutional frameworks toward a model of grassroots value construction rooted in lived social interactions. Empirically, it highlights the role of non-pesantren kiais as active agents of peacebuilding in multicultural contexts. Practically, the findings offer a contextual model of value-based religious leadership relevant for peace education and community-based conflict mitigation in pluralistic societies.